Development of extruded gluten free hard pretzel from brewer's rice - Paykary, Maryam (2014)
Rice (Oryza sativa) is a staple food for nearly one-half of the world population. Its production and consumption is mainly concentrated in Asian countries by approximately 95% of the world’s rice production. This amount of rice contributes to 40-80% of the Asian daily diet calories. The total world amount of harvested rice (paddy) was around 720 million tons in 2011. Broken rice which include chips and brewer’s rice constitutes about 1-17% of the total amount of paddy produced depending on the milling process and conditions. The brewer’s rice commercial usage, nowadays, is either for making wine or feeding livestock. The main goal of this study is to produce an extruded glutenfree pretzel-like snack for celiac people from brewer’s rice which in turns resulted in value adding of brewer’s rice, a low-value by-product of rice milling industry. Specifically, this study was conducted to re-optimize the basic materials in rice hard pretzel formulation and to improve the textural and physicochemical properties of the product by hydrocolloids addition. In the first part of the study, the main effect of seven basic materials on textural properties (cutting strength, breaking strength, crunchiness, and fracturability), surface color (L a and, b values), dimensional properties (lateral expansion, expansion ratio, and specific length), densities (bulk density, particle density, and material density), porosities (open porosity, close porosity, and total porosity), water reactions (water holding capacity, water solubility index, water absorption index), and oil reactions (oil holding capacity, oil absorption index) were studied in an attempt to choose the 20% of the most significant influential material to be optimized. Fresh yeast and sodium bicarbonate were the most significant factors affecting almost all of the properties studied. In the second part of the study, these factors were optimized in the new formula. Other formulation materials were fixed in order to obtain the required flavor. The result of RSM (Central Composite Design) showed that the best rice hard pretzel (optimal D = 47.22%) can be produced by adding 8.05g of fresh yeast and 2.59g of sodium bicarbonate for every 500g of brewer’s rice flour. Changes in formulation did not have any significant effect on pretzel surface colour (p>0.05). In the third part of the study, xanthan gum and hydroxy propyl methyl cellulose (HPMC) were added to the optimized basic formulation obtained from the first part of this study. Addition of soy lecithin as emulsifier at a concentration of 2% of the total fat was fixed throughout this section. Both the xanthan gum and HPMC were separately applied in a full factorial design with added water to determine the most suitable type and levels of hydrocolloid for producing the best rice hard pretzel. All the physico-chemical properties of the product as mentioned in part two above were evaluated. The HPMC was recommended as the most suitable hydrocolloid in this study due to wider application of concentration range compared to xanthan gum. The result showed that addition of 4.44-4.95g of HPMC and 153.5-178.6g of water for every 500g of brewer’s rice flour produces rice hard pretzel with the best textural and physico-chemical properties (p<0.05; optimal D=100.0%). The optimal experimental values of all 18 different textural, and physicchemical properties are as follows: cutting strength 12.392±0.747N, breaking strength 0.383±0.008N, crunchiness 14.334±1.528, fracturbility 3.533±0.0458mm, lateral expansion 52.11±1.57%, expansion ratio 1.547±0.006, specific length 7.774±0.194, bulk density 0.4663±0.0266g/ml, particle density 1.0987±0.0460g/ml, material density 1.4261±0.0092g/ml, open porosity 57.69±2.50%, close porosity 26.89±0.73%, total porosity 68.39±0.68%, WAI 6.3140±0.1087g/g, WSI 7.62±0.28%, WHC 4.5012±0.2339g/g, OAI 4.91±0.22ml/g, and OHC 0.83±0.04%. the final optimized gluten free rice hard pretzel formulation includes 67.633% brewer’s rice flour, 3.219% corn starch, 3.246% shortening, 0.034% ammonium bicarbonate, 0.007% soy lecithin, 0.352% sodium bicarbonate, 0.676% sodium chloride, 1.089% yeast, 0.625% HPMC, and 23.119% water.